Cooperative Iron-Brønsted Acid Catalysis: Enantioselective Hydrogenation of Quinoxalines and 2 H-1,4-Benzoxazines - Fleischer, Steffen; Zhou, Shaolin; Werkmeister, Svenja; Junge, Kathrin; Beller, Matthias (Chemistry : a European journal, 2013)
Come together! A selective Fe‐catalysed enantioselective reduction of quinoxalines and benzoxazines with hydrogen is demonstrated. Key to success is the combination of a chiral Brønsted acid and a well‐defined non‐chiral Fe hydrogenation catalyst. This methodology constitutes an attractive and environmentally favourable alternative to well‐established asymmetric hydrogenations by using precious‐metal‐based catalysts.